2021
DOI: 10.1038/s41374-021-00540-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based grading of ductal carcinoma in situ in breast histopathology images

Abstract: Ductal carcinoma in situ (DCIS) is a non-invasive breast cancer that can progress into invasive ductal carcinoma (IDC). Studies suggest DCIS is often overtreated since a considerable part of DCIS lesions may never progress into IDC. Lower grade lesions have a lower progression speed and risk, possibly allowing treatment de-escalation. However, studies show significant inter-observer variation in DCIS grading. Automated image analysis may provide an objective solution to address high subjectivity of DCIS gradin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
(65 reference statements)
2
13
0
Order By: Relevance
“…Consequently, the mean accuracies of the CNN models for three-class classification were increased than those for four-class classification. In other similar studies, the imbalanced datasets were used without a balancing strategy [ 33 , 34 ]. In the light of previous other studies and our experimental results, we concluded that the imbalance was not a critical issue in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the mean accuracies of the CNN models for three-class classification were increased than those for four-class classification. In other similar studies, the imbalanced datasets were used without a balancing strategy [ 33 , 34 ]. In the light of previous other studies and our experimental results, we concluded that the imbalance was not a critical issue in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning has been widely applied in computational histopathology, with applications such as cancer classification in WSIs, cell detection and segmentation, and the stratification of patient outcomes Yu et al (2016); Hou et al (2016); Madabhushi and Lee (2016); Litjens et al (2016); Kraus et al (2016); Korbar et al (2017); Luo et al (2017); Coudray et al (2018); Wei et al (2019); Gertych et al (2019); Bejnordi et al (2017); Saltz et al (2018); Campanella et al (2019); Iizuka et al (2020). For breast histopathology in particular, deep learning has been applied for classification of cancer in WSIs Bayramoglu et al (2016); Sharma and Mehra (2020); Hameed et al (2020); Mi et al (2021); Sohail et al (2021); Wetstein et al (2021). As for histopathological grading of differentiation level for DCIS, a deep learning-based DCIS grading system that achieved a performance similar to expert observer pathologists was reported Wetstein et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…For breast histopathology in particular, deep learning has been applied for classification of cancer in WSIs Bayramoglu et al (2016); Sharma and Mehra (2020); Hameed et al (2020); Mi et al (2021); Sohail et al (2021); Wetstein et al (2021). As for histopathological grading of differentiation level for DCIS, a deep learning-based DCIS grading system that achieved a performance similar to expert observer pathologists was reported Wetstein et al (2021). IDC classification has also been recently investigated Kanavati and Tsuneki (2021a).…”
Section: Introductionmentioning
confidence: 99%
“…The applications from cancer cells classification and segmentation and patient outcome predictions for a variety of organs and diseases [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Machine learning has been previously applied to various applications of breast histopathology classification [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%